World book 2001. Vol. 14 N-O / Mary Alice Anderson - Anderson, Mary Alice (2001)
Ethnic names, history of family names, other names, additional, rise to power important dates in napoleon´s life, first consul of France, the Napoleonic empire, fall from power, napoleon s place in history, united states gross national debt economic growth since the civil war, Canada national debt and economic growth since confederation in 1867, national park, natable national park systems, other interesting.